1997
DOI: 10.1111/1523-1747.ep12289718
|View full text |Cite
|
Sign up to set email alerts
|

Premature Termination Codons Are Present on Both Alleles of the Bullous Pemphigoid Antigen 2/Type XVII Collagen Gene in Five Austrian Families with Generalized Atrophic Benign Epidermolysis Bullosa

Abstract: Patients with generalized atrophic benign epidermolysis bullosa (GABEB), an inherited subepidermal blistering disease, often have no immunologically detectable bullous pemphigoid antigen 2 (BPAG2) in their epidermal basement membrane. Recently, we analyzed the BPAG2 gene (GenBank no. M91669) in an Austrian family with GABEB and identified a homozygous deletion mutation, 4003delTC, that results in a downstream premature termination codon (PTC). This mutation has now been identified in additional descendants, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 23 publications
3
49
0
Order By: Relevance
“…The proband, a 56-year-old woman, is a member of a large Austrian GABEB kindred that includes 5 affected and 5 unaffected siblings in 1 generation, as well as a pedigree that signifies propagation of the mutant allele through at least 6 generations (18,21). All 4 living affected siblings (1 affected having died in infancy because of complications of this inherited blistering disease) are homozygous for a 2-bp deletion in COL17A1, 4003delTC, and show the same homozygous haplotype for 5 intragenic COL17A1 polymorphisms (17,18,22). The proband's skin shows the same extent and character of blistering as that of her affected siblings; i.e., regions of nonfragile skin are not present.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proband, a 56-year-old woman, is a member of a large Austrian GABEB kindred that includes 5 affected and 5 unaffected siblings in 1 generation, as well as a pedigree that signifies propagation of the mutant allele through at least 6 generations (18,21). All 4 living affected siblings (1 affected having died in infancy because of complications of this inherited blistering disease) are homozygous for a 2-bp deletion in COL17A1, 4003delTC, and show the same homozygous haplotype for 5 intragenic COL17A1 polymorphisms (17,18,22). The proband's skin shows the same extent and character of blistering as that of her affected siblings; i.e., regions of nonfragile skin are not present.…”
Section: Methodsmentioning
confidence: 99%
“…In the largest GABEB kindred identified to date, affected individuals are homozygous for a 2-bp deletion, 4003delTC, which results in a frameshift and a premature termination codon (PTC) 86 bp downstream (17,18). This mutation results in nonsense-mediated mRNA decay that abolishes synthesis of type XVII collagen and accounts for the absence of this adhesion molecule in the epidermal BM of these patients (18). Interestingly, 1 affected individual in this large kindred showed focal areas of epidermal BM that stained positive for type XVII collagen by IF microscopy (9), suggesting revertant mosaicism as described above.…”
Section: Introductionmentioning
confidence: 99%
“…5 JEB-nH is caused by less deleterious mutations in the laminin 5 genes or by mutations in the gene encoding another protein, type 17 collagen. 5,6 JEB-H has also been called JEB-letalis, and as this moniker suggests, it is a lethal disease. According to the National Epidermolysis Bullosa Registry (NEBR), as of 1 December 1995, 9/22 (40.9%) enrolled JEB-H patients had died, with nearly 90% of deaths occurring before 1 year of age; and 51/148 (34.5%) enrolled JEB-nH patients had died.…”
Section: Introductionmentioning
confidence: 99%
“…Most COL17A1 mutations described to date are nonsense and deletion mutations leading to premature termination of translation and absence of type XVII collagen from the skin (Darling et al, 1997;Floeth et al, 1998;Gatalica et al, 1997;Jonkman et al, 1997;McGrath et al, 1995McGrath et al, , 1996aMcGrath et al, , 1996bScheffer et al, 1997;Schumann et al, 1997;Shimizu et al, 1998 887 acceptor splice-site mutations (Chavanas et al, 1997;Darling et al, 1998;Pulkkinen et al, 1999), one donor splice-site mutation (Pulkkinen et al, 1999), and four missense mutations (Floeth et al, 1998;McGrath et al, 1996a;Schumann et al, 1997;Tasanen et al, 2000) have been reported. In only one (Schumann et al, 1997) of the patients could type XVII collagen be immunologically detected in skin or cultured keratinocytes.…”
Section: Discussionmentioning
confidence: 99%